2016
DOI: 10.1073/pnas.1512307113
|View full text |Cite
|
Sign up to set email alerts
|

Chemotaxis toward phytoplankton drives organic matter partitioning among marine bacteria

Abstract: The microenvironment surrounding individual phytoplankton cells is often rich in dissolved organic matter (DOM), which can attract bacteria by chemotaxis. These "phycospheres" may be prominent sources of resource heterogeneity in the ocean, affecting the growth of bacterial populations and the fate of DOM. However, these effects remain poorly quantified due to a lack of quantitative ecological frameworks. Here, we used video microscopy to dissect with unprecedented resolution the chemotactic accumulation of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
213
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 209 publications
(231 citation statements)
references
References 46 publications
5
213
2
1
Order By: Relevance
“…As our results suggest that interactions of diatoms with MMA-degrading bacteria are profitable in marine environments, it appears to be an attractive hypothesis that diatoms may release molecules to attract methylamine-degrading bacteria. In agreement with this hypothesis, it has been shown that bacteria can employ chemotaxis to approach and get established within the phycosphere (8,(50)(51)(52). To our knowledge, molecules that specifically attract methylotrophic bacteria are not known so far.…”
Section: Discussionmentioning
confidence: 76%
“…As our results suggest that interactions of diatoms with MMA-degrading bacteria are profitable in marine environments, it appears to be an attractive hypothesis that diatoms may release molecules to attract methylamine-degrading bacteria. In agreement with this hypothesis, it has been shown that bacteria can employ chemotaxis to approach and get established within the phycosphere (8,(50)(51)(52). To our knowledge, molecules that specifically attract methylotrophic bacteria are not known so far.…”
Section: Discussionmentioning
confidence: 76%
“…A thin boundary layer of fluid termed 'the phycosphere' surrounds algal cells (Bell and Mitchell, 1972). In the phycosphere, molecular gradients are governed by diffusion (Lazier and Mann, 1989) and altered by the activities of bacteria that accumulate through chemotaxis (Stocker and Seymour, 2012;Smriga et al, 2016) and reproduction. As the thickness of diffusive boundary layers scales with surface area (Karp-Boss et al, 1996), larger phytoplankton may harbor more bacteria than smaller phytoplankton.…”
Section: Introductionmentioning
confidence: 99%
“…From the above equations (Eqs. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18], the maximum rate of growth is calculated from the slope as shown in the following table. From Table 3 it can be seen that the results of the maximum specific growth rate of heterotrophic bacteria show that the use of BI-2000 electrolyte respiration rate analyzer, the range is large and the range is roughly 7.72 d-1-10.05 d-1, the average is 8.6 d -1 compared with ASM1 model.…”
Section: Determination Of Yield Coefficient Of Heterotrophic Bacteriamentioning
confidence: 99%
“…Therefore, it is very important to determine the kinetic parameters of heterotrophic bacteria. As a method recommended by International Water Association (IWA), respiration measurement has applied successfully to the determination of stoichiometry and kinetic parameters of wastewater (Smriga et al, 2016) and for the determination of Chemical Oxygen Demand (COD) components .…”
Section: Introductionmentioning
confidence: 99%